"Upping the ante": how to design efficient auctions with entry?. (18th June 2013) - Lamy, Laurent
<x xml:space="preserve">Abstract</x> Of primary importance in auction design is the set of strategies available to the seller at the auction stage. We first formalize hold‐up regarding entry costs that preys on second‐price auctions when the seller may engage in a costly shill‐bidding activity. We derive the optimal reserve and show how shill bidding can make posted prices outperforming auctions. Second, we advocate for a new regulation where shills would be banned but with the possibility of canceling sales ex post, which offers some valuable flexibility: the English auction with jump bids implements, then, the first best in general environments.